2001
DOI: 10.1038/84145
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We have defined the structural and dynamic properties of an early folding intermediate of beta-lactoglobulin known to contain non-native alpha-helical structure. The folding of beta-lactoglobulin was monitored over the 100 micros--10 s time range using ultrarapid mixing techniques in conjunction with fluorescence detection and hydrogen exchange labeling probed by heteronuclear NMR. An initial increase in Trp fluorescence with a time constant of 140 micros is attributed to formation of a partially helical compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
104
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(111 citation statements)
references
References 35 publications
7
104
0
Order By: Relevance
“…More extended coil structures that are farther away from the native hairpin conformation are more likely to transiently fold to helical conformations, which, because they require the formation of only local contacts (47), are relatively easy to form provided that the side-chain secondary structure propensities do not strongly disfavor helix. ␣-helices have been experimentally observed as intermediates along the folding pathway of ␤-sheets in ␤-lactoglobulin (48,49). Some previous computational studies of the G peptide have reported ␣-helix content (15,16,32,39), whereas others have not (8,13,14,17,20).…”
Section: Discussionmentioning
confidence: 94%
“…More extended coil structures that are farther away from the native hairpin conformation are more likely to transiently fold to helical conformations, which, because they require the formation of only local contacts (47), are relatively easy to form provided that the side-chain secondary structure propensities do not strongly disfavor helix. ␣-helices have been experimentally observed as intermediates along the folding pathway of ␤-sheets in ␤-lactoglobulin (48,49). Some previous computational studies of the G peptide have reported ␣-helix content (15,16,32,39), whereas others have not (8,13,14,17,20).…”
Section: Discussionmentioning
confidence: 94%
“…in experimental (13)(14)(15) as well as computational studies using simplified approaches (16,17). Our results are obtained using first-principle all-atom Monte Carlo simulations.…”
Section: Resultsmentioning
confidence: 99%
“…ignificant advances in theory and experiment are producing an increasingly detailed description of how a polypeptide self-assembles into the native structure of a protein (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Energy landscape theories (1,(12)(13)(14)(15), in particular, have provided a framework for interpreting experimental investigations of protein folding kinetics.…”
mentioning
confidence: 99%